2006
DOI: 10.1002/sdr.348
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term and short‐term customer reaction: a two‐stage queueing approach

Abstract: We analyse a simple, deterministic queueing system with feedback. We model a customer's decision to seek service as a two-stage process: (1) deciding whether or not to use a facility (become a customer), and (2) deciding the frequency of use (daily, weekly, monthly, etc.). We consider both a constant and a deterministic, time-dependent usage pattern. We ignore variability, and focus on three forms of feedback: (1) the service rate increases as queue length increases; (2) the frequency with which customers use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Regarding the specific field of simulation, a review on agent-based simulation in marketing has showed that links with supply restrictions are usually not considered and that word-of-mouth analysis will be beneficial when included in simulation approaches [11]. Among the few manuscripts connecting simulation and CLV, the early work of Ackere et al [12] applied Monte Carlo simulations to evaluate customer reaction in a waiting line in the long term, although the model was deterministic. Hara et al [13] modeled the lead time for customer satisfaction using a customer satisfaction index, but the model did not allow for repeated consumption.…”
Section: Customer Lifetime Value In Supply Chain and Simulationmentioning
confidence: 99%
“…Regarding the specific field of simulation, a review on agent-based simulation in marketing has showed that links with supply restrictions are usually not considered and that word-of-mouth analysis will be beneficial when included in simulation approaches [11]. Among the few manuscripts connecting simulation and CLV, the early work of Ackere et al [12] applied Monte Carlo simulations to evaluate customer reaction in a waiting line in the long term, although the model was deterministic. Hara et al [13] modeled the lead time for customer satisfaction using a customer satisfaction index, but the model did not allow for repeated consumption.…”
Section: Customer Lifetime Value In Supply Chain and Simulationmentioning
confidence: 99%
“…Orjuela and Huertas (Orjuela & Huertas, 2004) Other models analyze attention capacities using perception parameters regarding the length of lines (Delgado, 2011), (Ann van Ackere, 2006). System Dynamics analyses contemplate models that use human capital and planning analysis to model service dynamics, in order to present models that evaluate public policies in Australia (Sveiby, 2002).…”
Section: Models Applied To Planningmentioning
confidence: 99%
“…However, there are a few papers going one step further. Haxholdt et al [9] and van Ackere et al [28] construct a queuing model with feedback and exhibit the phenomenon that the arrival rate depends on waiting time. They exploit some simulation methods with the decision variable of service rate.…”
Section: Literature Reviewmentioning
confidence: 99%